Pembangkit Gelombang Terprogram Menggunakan DDS AD9851 Berbasis Mikrokontroler 18F4550 - Wisnu Adji Kharisma; Hidayat Nur Isnianto (Universitas Syiah Kuala, 2014)
Direct Digital Synthesizer (DDS) applies a method to generate an analog waveform in a digital manner, which is formed by generating a digital signal that varies with time and converting it into analog form using a digital to analog device (DAC). IC AD9851 is an analog waveform generator to implement the DDS method, which generates a frequency that can be changed according to the needs of its users. The digital signal is generated using a PIC 18F4550 microcontroller that has a full-speed USB 2.0 feature to interface with the computer via USB without the need of special drivers to do the communication. Setting of the output frequency can be done via the keypad or buttons programmed via computer. The test results are a wide range of frequency waves produced from 100 Hz to 30 MHz in the form of a sine wave with an amplitude of 430 mV and a square wave with an amplitude of 4,125 V.Keywords: DDS, AD9851, PIC 18F4550, USB, function generator